Selective Cu Electrodeposition on Micrometer Trenches Using Microcontact Printing and Additives - Shim, Jinyong; Lee, Jinhyun; Yoo, Bongyoung (Archives of Metallurgy and Materials, 2021)
Selective deposition was performed on a micrometer trench pattern using a microcontact printing (μCP) process. Alkanethiols required for selective deposition were analyzed according to the carbon chain by linear sweep voltammetry (LSV). According to the LSV analysis, the effect of inhibiting Cu deposition depending on the length of the carbon chain was observed. During the Cu electrodeposition, the trench could be filled without voids by additives (PEG, SPS, JGB) in the plating solution. A μCP process suppressing the deposition of the sample was used for selective Cu electrodeposition. However, there was oxidation and instability of the sample and 1-hexadecanethiol in air. To overcome these problems, the μCP method was performed in a glove box to achieve effective inhibition.
Keywords: µCP; selective Cu deposition; RDL; overburden; SAM (alkanethiol); Additives